1983
DOI: 10.1002/aja.1001680303
|View full text |Cite
|
Sign up to set email alerts
|

The cytology of the dental follicle and adjacent alveolar bone during tooth eruption in the dog

Abstract: Previous studies from our laboratories have shown that premolar eruption in dogs depends upon the presence of the dental follicle and is independent of root or crown growth or attachment to the oral epithelium. The present study is an analysis of the cellular composition of the dental follicle and the cellular investment of the adjacent walls of the bony crypt before and during eruption of the third and fourth mandibular permanent premolars in young beagle dogs. Four premolar follicles and their adjacent bony … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
0
7

Year Published

1986
1986
2007
2007

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 112 publications
(73 citation statements)
references
References 17 publications
3
63
0
7
Order By: Relevance
“…Early cytological studies of dog premolars showed that, prior to the onset of eruption, there is an influx of mononuclear cells into the coronal portion of the dental follicle, with a concurrent increase in the numbers of osteoclasts in the coronal third of the alveolar bony crypts (Marks et al, 1983). This is followed by a sharp decrease in both mononuclear cell and osteoclast numbers.…”
Section: (C) Cellular Eventsmentioning
confidence: 99%
“…Early cytological studies of dog premolars showed that, prior to the onset of eruption, there is an influx of mononuclear cells into the coronal portion of the dental follicle, with a concurrent increase in the numbers of osteoclasts in the coronal third of the alveolar bony crypts (Marks et al, 1983). This is followed by a sharp decrease in both mononuclear cell and osteoclast numbers.…”
Section: (C) Cellular Eventsmentioning
confidence: 99%
“…To accomplish this requires the presence of the dental follicle, a loose connective tissue sac that surrounds the unerupted tooth. Specifically, mononuclear cells (osteoclast precursors) are recruited to the follicle [2,3] where they fuse to form osteoclasts for alveolar bone resorption of the eruption pathway. In the first mandibular molar of the rat, the maximal number of mononuclear cells and osteoclasts are seen at day 3 [3,4] and this correlates with the maximal gene expression of 2 chemotactic molecules in the follicle -colony stimulating factor-1 (CSF-1) [5] and monocyte chemotactic protein-1 (MCP-1) [6].…”
Section: Introductionmentioning
confidence: 99%
“…The major cellular event that occurs in the follicle just prior to or at the onset of prefunctional eruption (movement of tooth within the bony crypt) is an influx of mononuclear cells (monocytes) into the follicle (Marks et al, 1983;Wise et al, 1985Wise et al, , 1989. Concurrent with this is an increase in the number of osteoclasts in the bony crypt, osteoclasts that are required for the resorption of alveolar bone.…”
Section: Discussionmentioning
confidence: 99%